Faktor - faktor yang mempengaruhi Kinerja Sistem Informasi Akuntansi Pada Bank Panin di Bandar Lampung - Muhammad Luthfi; Yenni Yohanna; Eka Sariningsih (Universitas Malahayati, 2014)
Abstract. Along with the development of information technology in people's lives, to the demanding world of banking to improve information technology being used Panin Bank is a private bank that increases the use of its information system with a system of CBS (Core Banking System) to be able to provide good service or satisfaction of its customers. This research aims to examine and analyze the factors that affect the performace of the accounting information system at Panin Bank in Bandar Lampung. This research involves 50 respondents are spread across four branches of Panin Bank in Bandar Lampung. The data obtained through the dissemination of the questionnaire directly to the object of research. Data analysis using multiple linear regression and partial test/independent samples t-test. The results of this research show that there is a significant influence (positive) between free variables that factor user involvement in the development process of the system, the ability of personal system engineering, top management support, user training and education programs, to the variable bound to the performance of accounting information system.